Site-Specific Introduction of Negative Charges on the Protein Surface for Improving Global Functions of Recombinant Fetal Hemoglobin - Kettisen, Karin; Dicko, Cedric; Smeds, Emanuel; Bülow, Leif (Frontiers in Molecular Biosciences, 2021)
Due to its compatible oxygen-transporting abilities, hemoglobin (Hb) is a protein of interest in the development of artificial oxygen therapeutics. Despite continuous formulation attempts, extracellular Hb solution often exhibits undesirable reactions when applied in vivo. Therefore, protein engineering is frequently used to examine alternative ways of controlling the unwanted reactions linked to cell-free Hb solutions. In this study, three mutants of human fetal hemoglobin (HbF) are evaluated; single mutants αA12D and αA19D, and a double mutant αA12D/A19D. These variants were obtained by site-directed mutagenesis and recombinant production in E. coli, and carry negative charges on the surface of the α-subunit at the designated mutation sites. Through characterization of the mutant proteins, we found that the substitutions affected the protein in several ways. As expected, the isoelectric points were lowered, from 7.1 (wild-type) down to 6.6 (double mutant), which influenced the anion exchange chromatographic procedures by shifting conditions towards higher conductivity for protein elution. The biological and physiological properties of HbF could be improved by these small modifications on the protein surface. The DNA cleavage rate associated with native HbF could be reduced by 55 %. In addition, the negatively charged HbF mutant had an extended circulation time when examined in a mouse model using top load Hb additions. At the same time, the mutations did not affect the overall structural integrity of the HbF molecule, as determined by small-angle X-ray scattering. In combination with circular dichroism and thermal stability, modest structural shifts imposed by the mutations could possibly be related to changes in secondary structure or reorganization. Such local deformations were too minor to be determined within the resolution of the structural data; and overall, unchanged oxidation and heme loss kinetics support the conclusion that the mutations did not adversely affect the basic structural properties of Hb. We confirm the value of adding negatively charged residues onto the surface of the protein to improve the global functions of recombinant Hb.